Assessment of dermal exposure to pesticides among farmers using dosimeter and hand washing methods - Lari, Summaiya; Jonnalagadda, Padmaja R.; Yamagani, Praveen; Medithi, Srujana; Vanka, Janardhan; Pandiyan, Arun; Naidu, Mohan; Jee, Babban (Frontiers in Public Health, 2022)
Inappropriate use of pesticides followed by unsafe handling practices to control the insect infestation among the farming groups in developing countries has resulted in a high exposure risk. The use of personal protective equipment is also negligible among Indian farmers due to their affordability to access the same. Very little research has been conducted to establish an exposure assessment procedure through dermal penetration of pesticide residues. Therefore, to quantify the contamination of pesticide residues through dermal exposure along with detailed field observations and pesticide management practices, a field study was conducted in Rangareddy district, Telangana, Southern India, to assess the dermal exposure based on dosimeter and hand washing methods. The analytical method was modified and validated in-house for performance parameters such as limit of detection, quantification, linear range, recovery, and precision. The potential dermal exposure values ranged from 0.15 to 13.45 μg, while a reduction was found in exposure levels as actual dermal exposure values ranged from 0 to 0.629 μg. Contamination through hand washing was the major contributor to overall dermal exposure. Statistical analysis revealed a significant difference in the exposed dermal regions of the leg and torso after the use of PPE. Penetration factor for each anatomical region and risk evaluation in terms of the Margin of Safety implies unsafe handling of pesticides. The findings of the present study confirm the increased exposure to organophosphate pesticides among operators and highlight the importance of the use of protective measures, especially among those that focus on dermal exposure mitigation.